[tex]\bf a)\ \ \dfrac{^{7)}4}{\ \ 3}+\dfrac{^{3)}5}{\ \ 7}=\dfrac{28+15}{21}=\dfrac{43}{21}=2\dfrac{1}{21}\\ \\ \\ d)\ \ \dfrac{5}{7}+\dfrac{4}{3}=\dfrac{^{7)}4}{\ \ 3}+\dfrac{^{3)}5}{\ \ 7}=\dfrac{28+15}{21}=\dfrac{43}{21}=2\dfrac{1}{21}\\ \\ \\ b)\ \ \dfrac{^{4)}2}{\ \ 7}+\dfrac{^{7)}1}{\ \ 4}=\dfrac{8+7}{28}=\dfrac{15}{28}\\ \\ \\ c)\ \ \dfrac{^{9)}5}{\ \ 8}-\dfrac{^{8)}5}{\ \ 9}=\dfrac{45-40}{72}=\dfrac{5}{72}[/tex]
[tex]\bf e)\ \ \dfrac{^{9)}1}{\ \ 4}+\dfrac{^{4)}2}{\ \ 9}=\dfrac{9+8}{36}=\dfrac{17}{36}[/tex]